Urban Sprawl Analysis in Kutupalong Refugee Camp, Bangladesh - Loncar, Filip (2022)
Loncar, F., & Cabral, P. (2022). Urban Sprawl Analysis in Kutupalong Refugee Camp, Bangladesh. In C. Grueau, & L. Ragia (Eds.), Proceedings of the 8th International Conference on Geographical Information Systems Theory, Applications and Management: GISTAM 2022 (Vol. I, pp. 83-90). (8th International Conference on Geographical Information Systems Theory, Applications and Management (GISTAM 2022), 27th to 29th April 2022, Online Streaming). SciTePress - Science and Technology Publications. https://doi.org/10.5220/0000149600003185